Role of T Cell Receptor Affinity in the Efficacy and Specificity of Adoptive T Cell Therapies - Stone, Jennifer D.; Kranz, David (Frontiers in Immunology, 2013)
Over the last several years, there has been considerable progress in the treatment of cancer using gene modified adoptive T cell therapies. Two approaches have been used, one involving the introduction of a conventional alpha-beta T cell receptor (TCR) against a pepMHC cancer antigen, and the second involving introduction of a chimeric antigen receptor (CAR) consisting of a single-chain antibody as an Fv fragment (scFv) linked to transmembrane and signaling domains. In this review, we focus on one aspect of TCR-mediated adoptive T cell therapies, the impact of the affinity of the alpha-beta TCR for the pepMHC cancer antigen on both efficacy and specificity. We discuss the advantages of higher affinity TCRs in mediating potent activity of CD4 T cells. This is balanced with the potential disadvantage of higher affinity TCRs in mediating greater self-reactivity against a wider range of structurally similar antigenic peptides, especially in synergy with the CD8 co-receptor. Both TCR affinity and target selection will influence potential safety issues. We suggest pre-clinical strategies that might be used to examine each TCR for possible on-target and off-target side effects due to self-reactivities, and to adjust TCR affinities accordingly.